Demographics and Clinical Characteristics of Adult Patients Hospitalized due to COVID-19 in a Rural/Suburban Integrated Health System in Southcentral Pennsylvania, March Through May 2020. (16th March 2021) - Bohrn, Michael A; Benenson, Ronald; Bush, Chelsea M; Bell, Theodore; Black, Cassandra; Doan, Binh; Green, Cindy; Mass, Matthew M; Newell, Jacklyn A; Rowe, Jessica; Schlenker, Melissa K; Schuchardt-Peet, Claudia; et al.
Abstract: Existing characterizations of coronavirus disease 2019 (COVID-19) admissions have occurred primarily in urban settings. This report describes demographic and clinical characteristics of the first COVID-19 patients presenting to a 6-hospital integrated health care system in rural/suburban southcentral Pennsylvania. Medical records of adult patients admitted with COVID-19 between March and May of 2020 were retrospectively reviewed for demographics, symptomatology, imaging, and lab values. Results were largely consistent with previous studies, although gastrointestinal manifestations were more prevalent, with diarrhea reported in 25.4% of patients hospitalized due to COVID-19. Nursing home patients represented 10.1% of admissions but accounted for 35.5% of total deaths in our sample. Patients self-identifying as Hispanic were disproportionately affected. Although Hispanic ethnicity was self-reported in only 9% of the community population, Hispanic patients accounted for 34% of admissions. Our data provide a unique focused review of hospitalized COVID-19 patients in a rural/suburban setting.